The unethical impact of creative accounting on the financial performance of companies OLYMPUS SCANDAL - Aldurrah Waleed Khalid, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The motivation behind this examination is about the risks of utilizing what is known as inventive bookkeeping as a result of its effect on decorating fiscal reports and indicating them in an unreasonable manner, which was the reason for the worldwide monetary emergency that hit the economies of the creating and created world the same. The utilization of innovative bookkeeping with its perceived techniques prompts an absence of unwavering quality in the budget summaries, which significantly affects the assessment and choice of the inner and outer client of the organizations and associations put resources into, and therefore the effect on the monetary situation of the organization in the currency market and its deficiency of intensity in the realm of business